Post occupancy evaluation of private housing in Pakistan - Chohan A.H.,; Hashim A.E.,; Ramly A.,; Che-Ani A.I,; Ishak N.H, (Penerbit UKM, 2008)
Need of housing and need of quality housing are two issues which remained the subject of research and interest to researchers’ and designers’. Whenever designers complete projects, they are not fully aware of the consequences of their designs. Only through a post occupational survey, the designer usually realizes the mistakes or bad decisions they have taken during the design process. Unfortunately, such unforeseen conditions are the part of daily life for end users of residential buildings in developing regions. The main purpose of this research is to understand and identify the causes of design deficiencies and their effects on residential buildings at post occupational stage in Karachi, Pakistan. Housing designs need to be closely monitored and need to be synchronized with well tested and established criteria and standards of housing. Other factors which influence the housing design and quality, to name a few, are high price of land, institutional control and unqualified personnel. This research circumscribes the issues and problems faced by the users of private housing at post occupational stage, which have resulted from deficient designs. These problems affect the users from unplanned maintenance to major repairs leading to danger of collapse. In order to evaluate these effects on buildings, a case study was conducted in low and medium cost housing stock in Karachi, a metropolitan city of Pakistan. The data for research was collected and analysed through computation and interpreted to understand the far reaching effects and implications of design deficiencies in low and medium cost housing stocks of Karachi